Reconstruction of Ownership Rights of Apartment Unit Built on Land with Building Rights - Abraham Yazid Martin; Nova Monaya; Zainal Arifin Masruri (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This article examines the legal complexities of apartment units constructed on Building Rights (Hak Guna Bangunan, HGB) land in Indonesia, especially where HGB overlays State Land (Hak Pengelolaan Lahan, HPL). The current legal regime, grounded in Law No. 20 of 2011 on Flats and Government Regulation No. 18 of 2021, exposes vulnerabilities in the Horizontal Ownership of Strata Rights System (HMSRS) due to HGB’s temporal limitations. These constraints undermine strata ownership security, complicate land administration, and erode investor and occupant confidence. Using doctrinal and comparative methods, the study analyzes statutory frameworks, including Government Regulations No. 4 of 1988 and No. 40 of 1996, alongside post-Omnibus reforms. It situates the discussion within Indonesian agrarian law, property theory, and international apartment scholarship, highlighting tensions with constitutional mandates on social justice and equitable land use (Articles 28D(1), 28H, 33(3), and 34, 1945 Constitution). The article proposes a legal reconstruction model separating apartment units from underlying building rights via independent building certificates and a dedicated cadaster, enhancing legal certainty and aligning with modern land administration principles. This framework addresses gaps in strata governance, promoting legal resilience, investor protection, and social equity amid Indonesia’s agrarian reforms and urbanization.